Evaluasi Keberhasilan F-Learn Menggunakan Human Organization Technology (HOT) Fit Model pada Universitas Kristen Satya Wacana - Kezia Sharent Kodoati; Kristoko Dwi Hartomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Flexible Learning (F-Learn) is an online learning media support facility that is used to support the lecture process at SWCU. The purpose of this study is to evaluate the success rate of F-Learn implementation using the HOT Fit model and see which factors have a significant influence between Human, Organization, Technologicaland Net Benefit. This type of research was carried out with a quantitative approach, and data analysis using SEM PLS with the tools used, namely SmartPLS 3.0 in testing validity, reliability and hypothesis testing. The data was obtained through the results of distributing questionnaires and interviews with several lecturers, so that it is known that user satisfaction on human factors greatly influences the benefits of F-Learn. The results obtained from hypothesis testing there are 12 hypotheses, 8 accepted hypotheses and 4 rejected hypotheses. The success of the implementation of the system is declared a success, where the value of the usefulness of the system at the level of 70.8% is included in the strong category.